A high-performance method for direct determination of ultra-trace REEs in geological samples by ICP-MS using a designed heating-condensing system. Issue 4 (12th February 2021) - Yu, Jiaxin; Zhao, He; He, Tao; Luo, Tao; Zhang, Wen; Zong, Keqing; Lin, Jie; Liu, Yongsheng; Hu, Zhaochu
Abstract : Our results firstly indicate that the geometry of the skimmer cone has an important effect on signal enhancement when using a heating-condensing system in ICP-MS. Abstract : High sensitivity and minimized spectral interference are prerequisites for precise and accurate measurement results of ultra-trace REEs (Sc and Y, rare earth elements) in geological samples ( e.g., carbonates and peridotites). In this study, we designed a heating-condensing system for the direct determination of mass fractions of ultra-trace REEs in carbonates and peridotites by Ar–N2 mixed plasma ICP-MS combined with different skimmer cones. Compared to those under normal conditions (without a heating-condensing system), the signal sensitivities of the investigated 47 elements were improved by 5–8 and 6–24 fold at a heating temperature of 180 °C when using the H skimmer cone and the X skimmer cone, respectively. Our results firstly indicate that the geometry of the skimmer cone has an important effect on signal enhancement when using the heating-condensing system in ICP-MS. The addition of nitrogen (3–9 ml min −1 ) in the central channel of the plasma was found to significantly reduce the oxide ratios (CeO + /Ce + ) by a factor of approximately 5–10. This reduction is important for the determination of ultra-trace REEs, which are well known to be interfered by oxides of Ba and light REEs. We successfully applied this method to directly determine ultra-trace REEs in eight reference carbonates and peridotites. This simple and rapid method shows great potential for the direct determination of ultra-trace REEs in geological samples and other technogenic materials with a high matrix and low REE abundances.